2021
DOI: 10.33448/rsd-v10i14.22278
|View full text |Cite
|
Sign up to set email alerts
|

Doença renal crônica: doença subdiagnosticada? Análise epidemiológica em um centro de diálise

Abstract: A doença renal crônica (DRC), caracterizada pela diminuição progressiva da função renal, tem importância e prevalência elevada, mas muitos pacientes são diagnosticados tardiamente, quando a terapia renal substitutiva (TRS) é mandatória, tornando o rastreio da doença valioso para avaliação clínica. Este estudo objetiva analisar a quantidade de pacientes com diagnóstico de DRC de etiologia indeterminada, bem como o tempo decorrido entre a data de diagnóstico da DRC e o início da TRS, salientando a importância do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…A study by Vanelli et al (2018) 14 designed to screen patients for CKD based on the Screening for Occult Renal Disease (SCORED) tool found that albuminuria was present in a small number of individuals, suggesting that albuminuria testing has been underused in primary care to screen patients for CKD. Dumont et al (2021) 15 looked into the charts of 177 patients seen at a dialysis center and found that 20.3% had been diagnosed with CKD on the day they were started on renal replacement therapy. Given the asymptomatic progression of CKD, it is essential to screen populations at risk for the disease, such as individuals with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Vanelli et al (2018) 14 designed to screen patients for CKD based on the Screening for Occult Renal Disease (SCORED) tool found that albuminuria was present in a small number of individuals, suggesting that albuminuria testing has been underused in primary care to screen patients for CKD. Dumont et al (2021) 15 looked into the charts of 177 patients seen at a dialysis center and found that 20.3% had been diagnosed with CKD on the day they were started on renal replacement therapy. Given the asymptomatic progression of CKD, it is essential to screen populations at risk for the disease, such as individuals with type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant prevalence of use of nephroprotective medication, about 40% of the patients with kidney involvement were not on drugs of this class. A study enrolling 177 patients from a dialysis center found that 63.2% of the patients did not undergo conservative therapy with nephroprotective medication 15 . Nephroprotective drugs promote the vasodilation of afferent arterioles, thereby decreasing glomerular filtration and glomerular filtration pressure and introducing a nephroprotective effect in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Desses, 90 mil estão em diálise (processo de artificial para remover os resíduos e excesso de líquidos do corpo, geralmente quando a função renal está em 10% de funcionamento), número que cresceu mais de 100% nos últimos dez anos (Brasil, 2019). Em 2017, o número de indivíduos em diferentes estágios de DRC ultrapassou o número de casos de diabetes, osteoartrite e doença pulmonar obstrutiva crônica (DPOC) (Dumont et al, 2021).…”
Section: Introductionunclassified